2006
DOI: 10.1111/j.1439-0523.2006.01192.x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of useful traits in cassava grown in subhumid conditions

Abstract: A diallel study among nine parental clones of cassava was conducted in the subhumid environment on the northern coast of Colombia. Analysis of variance suggested significant effects for the six variables analysed: fresh-root yield, harvest index, root dry matter content, height of first branching, reaction to thrips and plant-type scores. General and specific combining ability effects and their interaction with the environment were significant for most of the variables as well. Results suggested that dominance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
9
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 35 publications
(43 reference statements)
7
9
0
5
Order By: Relevance
“…We then assessed the accuracy of genomic prediction of additive compared to total (additive plus nonadditive) genetic value. Using several approaches and datasets based on genome-wide marker data, we confirmed previous findings in cassava based on diallel crosses nonadditive genetic variation is significant, especially for yield traits (Cach et al 2005, 2006; Calle et al 2005; Jaramillo et al 2005; Pérez et al 2005a,b; Zacarias and Labuschagne 2010; Kulembeka et al 2012; Tumuhimbise et al 2014; Ceballos et al 2015; Chalwe et al 2015). A potential weakness of the marker system we used (GBS) is that it generates a high proportion of missing marker data and it may undercall heterozygotes when read depth is insufficient.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We then assessed the accuracy of genomic prediction of additive compared to total (additive plus nonadditive) genetic value. Using several approaches and datasets based on genome-wide marker data, we confirmed previous findings in cassava based on diallel crosses nonadditive genetic variation is significant, especially for yield traits (Cach et al 2005, 2006; Calle et al 2005; Jaramillo et al 2005; Pérez et al 2005a,b; Zacarias and Labuschagne 2010; Kulembeka et al 2012; Tumuhimbise et al 2014; Ceballos et al 2015; Chalwe et al 2015). A potential weakness of the marker system we used (GBS) is that it generates a high proportion of missing marker data and it may undercall heterozygotes when read depth is insufficient.…”
Section: Discussionsupporting
confidence: 85%
“…, specific combining ability) are strong, particularly for root yield traits (Cach et al 2005, 2006; Calle et al 2005; Jaramillo et al 2005; Pérez et al 2005a,b; Zacarias and Labuschagne 2010; Kulembeka et al 2012; Tumuhimbise et al 2014; Ceballos et al 2015; Chalwe et al 2015). If the limited number of parents tested thus far represents the broader cassava breeding germplasm, genetic gains, especially for already low-heritability root yield traits, will be slow regardless of the breeding scheme employed ( e.g.…”
mentioning
confidence: 99%
“…These findings confirm the conclusions of numerous diallelic studies conducted with both Latin American (Cach et al 2005(Cach et al , 2006Calle et al 2005;Jaramillo et al 2005;Pérez et al 2005a,b) and African cassava (Zacarias and Labuschagne 2010;Kulembeka et al 2012;Tumuhimbise et al 2014;Chalwe et al 2015) germplasm (see also Ceballos et al 2015). In agreement with the findings of Ly et al (2013), we found cassava mosaic disease severity (MCMDS) to be well predicted with an additive only model.…”
Section: Discussionsupporting
confidence: 81%
“…We then assessed the accuracy of genomic prediction of additive compared to total (additive plus nonadditive) genetic value. Using several approaches and datasets based on genome-wide marker data, we confirmed previous findings in cassava based on diallel crosses nonadditive genetic variation is significant, especially for yield traits (Cach et al 2005(Cach et al , 2006Calle et al 2005;Jaramillo et al 2005;Pérez et al 2005a,b;Zacarias and Labuschagne 2010;Kulembeka et al 2012;Tumuhimbise et al 2014;Ceballos et al 2015;Chalwe et al 2015). A potential weakness of the marker system we used (GBS) is that it generates a high proportion of missing marker data and it may undercall heterozygotes when read depth is insufficient.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation